2018
DOI: 10.1177/1358863x18770275
|View full text |Cite
|
Sign up to set email alerts
|

Depression and long-term prognostic outcomes following peripheral endovascular interventions in the VA Healthcare System

Abstract: The association between depression and peripheral artery disease (PAD) outcomes remains widely understudied. In patients with PAD undergoing a peripheral vascular intervention (PVI) who have a recent diagnosis of depression, it is unknown what their long-term outcomes are and what factors may mediate an adverse risk. We therefore studied 797 consecutive patients undergoing PVI across 33 Veterans Affairs (VA) centers. Depression and outcomes were documented from patients' medical records. Outcomes included: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In addition, the occurrence of ISR not only makes the patient feel physical pain but also increases the negative psychological mood and reduces happiness. Depression is a common negative psychological mood in patients with arterial disease 14 . Resting pain leads to poor sleep at night, causing anxiety, fear, and other bad emotions 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the occurrence of ISR not only makes the patient feel physical pain but also increases the negative psychological mood and reduces happiness. Depression is a common negative psychological mood in patients with arterial disease 14 . Resting pain leads to poor sleep at night, causing anxiety, fear, and other bad emotions 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire with SF-12 scale showed that the lowest, highest, and average PCS scores of 72 ISR patients were 20.24, 54.84, and 35.97±10 14. points, respectively, and the lowest, highest, and average MCS scores were 19.37, 59.78, and 38.09±10.53 points, respectively.…”
mentioning
confidence: 97%
“…24 Looking at the same VA population but focusing only on patients undergoing catheter-based peripheral vascular intervention, Smolderen et al found that the incidence of depression was almost same as ours, around 33%. 11 In our cohort we also included patients undergoing bypass operation, and this constituted about 32% of the total population, which is significant given that this patient population usually has a higher disease burden and is more functionally impaired.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Surgical intervention is indicated for patients with life-limiting short distance claudication after failure of medical management, rest pain, and/or tissue loss. 3 In previous publications, depression has been identified as a significant risk factor for development of PAD, also affecting the functional performance on this population, 6,7 and is associated with worse outcomes after intervention [8][9][10][11][12] ;however, these studies were conducted on patients from the Veterans Affairs (VA) system which is not representative of the population on a "real world" vascular practice.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment for PAD emphasize improving quality of life and decreasing the risk of new cardiovascular disease events, mainly through pharmacotherapy and revascularization procedures [11] . Recently in a study of 797 consecutive patients undergoing peripheral vascular intervention across 33 Veterans Affairs centers, depressed patients had higher rates of non-fatal cardiovascular events compared to patients without depression [12] . In addition to increasing the risk of PAD, depression also appears to impact the functional status and symptoms of patients with PAD.…”
Section: Discussionmentioning
confidence: 99%